The prevalence of narrow-a gle in adults javanese population in yogyakarta territory - Rose Suhardjo (Berita Kedokteran Masyarakat (BKM), 2005)
Background: Regarding the eye problem caused by narrow-angle that may be undetected or untreated, a database should be collected. Narrow angle in adult is a risk factor of glaucoma. The data of narrow-angle in adult population in Indonesia are lacking. Objective: To estimate the prevalence of narrow-angle according to the van Herick grading and ratio in Javanese population. Method: A cross the sectional study, community based ophthalmology study was carried out in Yogyakarta. One thousand two hundred twenty two (1222) adults aged 20 years and older were selected by stratified random sampling from each village of 18 subdistricts and examined at a KOWA SL15 portable slit lamp. The anterior chamber depth was graded according to the Van Herrick standard protocol. Grades I and 2 were classified as narrow-angled eyes. Result: Of 1222 subjects, 98 eyes (48 right eyes and 50 left eyes) of 50 subjects were diagnosed as narrow angle. The prevalence rate was 4.1%. The subjects were 13 men, and 37 women. The number of narrow-angle eyes increased with age 40 years and older for both men and women (OR = 2.77, 95% Cl 1.09-7.09). Conclusion: There are significantly more patients with upper van Herrick ratios or grades in Javanese population. The Van Herrick ratio increases with age and narrow-angle glaucoma occurs more frequent in women more than in men. Keywords: Narrow-angle, adult population, Van Herrick procedure, Yogyakarta territory